The Effect of Phytobiotics, Organic Acid and Humic Acids on the Utility and Egg Quality of Laying Hens - Henrieta Arpášová; Branislav Gálik; Veronika Pistová; Martin Fik (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of this study was the assessment of an influence of supplement of dietary herbal additive in combination with organic acids into feed mixture or drinking water of laying hens on performance parameters and egg quality. The Lohmann Brown Lite laying hens (n=30) were divided into 3 groups (n=10), and fed for 20 weeks ad libitum with complete feed mixtures (CFM). Hens in the control group received the complete feed mixture (CFM) and drank drinking water without any supplements. In the first experimental group hens received CFM without supplements but phytobiotics (bergamot oil (Citrus bergamia), thyme (Thymus vulgaris), clove (Syzygium aromaticum), pepper (Piper nigrum) in combination with the fumaric acid and citric acid at 60 mg per 1 liter of water were added to their drinking water. In the second experimental group was CFM enriched with humic acids in the concentration of 0.5%, and phytobiotcs with organic acids at the same dose as in the first experimental group were added to their drinking water. Monitored parameters: body weight (g), egg production (%), the weight of all produced eggs (g), egg albumen weight (g), egg albumen index, Haugh unit (HU), egg yolk weight (g), egg yolk index, egg yolk colour (°HLR), egg shell weight (g) and egg shell strength (N.cm-2). The results showed no significant differences between the both experimental groups and the control group in the parameter body weight of hens (P>0.05). The highest average body weight was found in the hens from the second experimental group (values in the order of groups: 1792.22±80.85; 1768.42±55.55; 1820.1±78.56 g±S.D.). We observed positive trend of increasing of egg production by adding of used supplements, especially in the second experimental group with the addition of humic acids, although with no statistically significant difference compared to the control group (P>0.05). The mean laying intensity in the order of groups: 90.42; 91.16; 91.56%. We observed statistically significant differences in the quality of egg albumen indicators (P≤0.05), specifically in the egg albumen index (the value in the order of groups: 84.02±16.04, 85.93±16.69, 87.44±18.41) and Haugh units (79.89±7.24, 80.58±7.62, 82.53±12.88 HU) in favour of the second experimental groups. Yolk index was not significantly higher in the second experimental group (P>0.05). In other parameters of yolk quality and eggshell quality, monitored values were comparable to those in the control group.